Ammonium tetrathiomolybdate treatment of copper‐associated hepatopathy in dogs. (18th March 2019) - Langlois, Daniel K.; Querubin, Janice R.; Schall, William D.; Nelson, Nathan C.; Smedley, Rebecca C.
Abstract: Background: Copper‐associated hepatopathy (CAH) is a common cause of liver disease in dogs. Althoughd ‐penicillamine can be an effective treatment, some dogs fail treatment or develop adverse effects. Ammonium tetrathiomolybdate (TTM) has been used to treat pathologic copper accumulation in other species, but its therapeutic potential for CAH is unknown. Objectives: To investigate short‐term safety and efficacy of TTM for treatment of CAH. Animals: Ten dogs with CAH. Methods: Prospective study. All dogs were treated with TTM PO for 6 weeks, and hepatic biopsies were performed after the treatment course. Dog experiencing initial decreases in hepatic copper concentrations ([Cu]H ) received 6 additional weeks of TTM treatment and underwent 1 additional biopsy. Physical and laboratory examinations were performed every 2 weeks for study duration. Results: Eight of 10 dogs had decreases in [Cu]H . Compared to baseline (median, 1606 μg/g; range, 572‐5158 μg/g), [Cu]H were decreased at 6 weeks (1033 μg/g, 450‐2975 μg/g; P  = .04) and 12 weeks (931 μg/g, 218‐1677 μg/g; P  = .02). Hepatic molybdenum concentrations increased >50‐fold ( P  < 0.001). Changes in histologic scores and hematologic and biochemical test results were variable and not significantly different from baseline. One dog developed presumed immune‐mediated anemia and thrombocytopenia, but it was unclear if this was related to TTM administration. Conclusions and Clinical Importance: Results suggest that TTM can effectively decrease [Cu]H in some dogs with CAH. Larger studies are needed to determine the overall safety and efficacy of TTM for treating CAH and how it compares with current treatments.